Davidson's self-assessment in medicine - Wake, Deborah; Cantley, Patricia (Elsevier, 2018)
This book is an excellent broad assessment text and forms a highly useful complement to the main textbook. It will help students increase the efficiency with which they acquire the factual knowledge necessary for both passing examinations and good medical practice.